Antenatal maternal hypoxia: criterion for fetal growth restriction in rodents - Jang, Eeun Amy; Longo, Lawrence D.; Goyal, Ravi (Frontiers in Physiology, 2015)
Rodents are a useful model for life science research. Accumulating evidence suggests that the offspring of mice and rats suffer from similar disorders as humans when exposed to hypoxia during pregnancy. Importantly, with antenatal hypoxic exposure, human neonates demonstrate low birth weight or growth restriction. Similarly, with antenatal hypoxic exposure rodents also demonstrate the fetal growth restriction (FGR). Surprisingly, there is no consensus on the minimum duration or degree of hypoxic exposure required to cause FGR in rodents. Thus, we have reviewed the available literature in an attempt to answer these questions. Based on studies in rats, birth weight reduction of 31% corresponded to 10th percentile reduction in birth weight curve. With the similar criterion (10th percentile), in mice 3 days or more and in rats 7 days or more of 14% or lower hypoxia administration was required to produce statistically significant FGR.